The celebration of Inti Raymi in Spain. Tinkuy and interculturality - Pinilla Pulido, Ana Leonilde (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
Inti Raymi is one of the most important celebrations for the Andean and Latin American populations, and particularly for their Indigenous nations and peoples. It celebrates the renewal of time and the relationship between humans and nature. Coming from the Andean culture, it is performed today all over the world. In this article I approach this ceremony held today in the Retiro park in Madrid. I analyze the celebration as a festivity that connects the present time and its location in Europe, with the space of the Andean world, with a temporality of more than five hundred years. The celebration of Inti Raymi in Madrid is a meeting where Andean migrants claims their local citizenship. In turn, the Andean ritual nature of the ceremony consecrates the space that, by becoming sacred, destabilizes the order that modernity has imprinted on the park and the city. The opportunity is created, then, for a meeting based on mutual recognition and the shared will to co-build and co-inhabit the world. This process is called “tinkuy” in the Kichwa language. From there, I discuss the management models of cultural diversity, pluralism and interculturality, putting them in dialogue with a perspective that broadens to encompass relationships with beyond even the human.